Accuracy of visual inspection with acetic acid and with Lugol's iodine for cervical cancer screening: Meta‐analysis. Issue 9 (26th May 2015) - Qiao, Liang; Li, Bo; Long, Mei; Wang, Xiao; Wang, Anrong; Zhang, Guonan
Abstract The aim of this review was to provide an updated summary estimation of the accuracy of visual inspection with acetic acid (VIA) and with Lugol's iodine (VILI) in detecting cervical cancer and precancer. Studies on VIA/VILI accuracy were eligible in which VIA/VILI was performed on asymptomatic women who all underwent confirmatory testing of histology, combination of colposcopy and histology, or combination of multiple screening tests, colposcopy and histology, to detect cervical intraepithelial neoplasia grade 2 or worse (CIN2+ or CIN3+). A bivariate model was fitted to estimate the accuracy of VIA/VILI and provide estimates of heterogeneity. Subgroup analysis was used to investigate the source of heterogeneity. A total of 29 studies on VIA and 19 studies on VILI were included finally in the meta‐analysis. The summary sensitivity and specificity of VIA for CIN2+ were 73.2% (95%CI: 66.5–80.0%) and 86.7% (95%CI: 82.9–90.4%), respectively, and those for VILI were 88.1% (95%CI: 81.5–94.7%) and 85.9% (95%CI: 81.7–90.0%), respectively. VIA and VILI were both more sensitive in detecting more severe outcome, although there was a slight loss in specificity. Apparent heterogeneity existed in sensitivity and specificity for both VIA and VILI. High sensitivity of both VIA and VILI for CIN2+ was found when a combination of colposcopy and histology was used as disease confirmation. VIA, VILI, even a combination of them in parallel, could be good options for cervical screening in low‐resource settings. Significant differences in sensitivity between different gold standards might provide a proxy for optimization of ongoing cervical cancer screening programs.